2020
DOI: 10.1016/j.cjco.2020.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Discussions in Antithrombotic Therapy Management in Patients With Atrial Fibrillation: A Delphi Consensus Panel

Abstract: Background In recent years, direct-acting oral anticoagulants (DOACs) have entered clinical practice for stroke prevention in non-valvular atrial fibrillation or prevention and treatment of venous thromboembolism. However, remaining uncertainty regarding DOAC use in some clinical scenarios commonly encountered in the real world has not been fully explored in clinical trials. Methods We report on use of a Delphi consensus process on DOAC use in non-valvular atrial fibril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 80 publications
(97 reference statements)
0
3
0
2
Order By: Relevance
“…Therefore, greater efforts to improve the prescription of OACs in the elderly are necessary, especially among older subjects with ACS and AF. It was recommended by consensus that a short course of dual therapy with OAC and an antiplatelet agent (preferably P2Y 12 ) should be considered as a preferred antithrombotic strategy in the therapeutic process of patients with both ACS and AF ( 9 , 33 ), and OAC should be applied in the long term of the patients' antithrombotic procedure ( 9 ). In our study, we found that even after a long-term follow-up of 5 years, OACs could still safely reduce mortality in elderly patients with both ACS and AF.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, greater efforts to improve the prescription of OACs in the elderly are necessary, especially among older subjects with ACS and AF. It was recommended by consensus that a short course of dual therapy with OAC and an antiplatelet agent (preferably P2Y 12 ) should be considered as a preferred antithrombotic strategy in the therapeutic process of patients with both ACS and AF ( 9 , 33 ), and OAC should be applied in the long term of the patients' antithrombotic procedure ( 9 ). In our study, we found that even after a long-term follow-up of 5 years, OACs could still safely reduce mortality in elderly patients with both ACS and AF.…”
Section: Discussionmentioning
confidence: 99%
“…Recent guidelines recommended that a short course of dual therapy with OAC and an antiplatelet agent (preferably P2Y12) should be considered as a preferred antithrombotic strategy in the therapeutic management of patients with both ACS and AF [ 8 , 34 ]. However, no guidelines have been published for OACs in patients with SCAD and AF [ 8 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent guidelines recommended that a short course of dual therapy with OAC and an antiplatelet agent (preferably P2Y12) should be considered as a preferred antithrombotic strategy in the therapeutic management of patients with both ACS and AF [5,31]. However, no guidelines have been published for OACs in patients with SCAD and AF [5,32].…”
Section: Discussionmentioning
confidence: 99%